Retrieval of separated instrument with instrument removal system - Sanjeev Kunhappan; Neerja Kunhappan; Sanjay Patil; Pratibha Agrawal (Wolters Kluwer Medknow Publications, 2012)
One of the most frequent endodontic mishaps is the separation of the endodontic instrument in the root canal. The separation influences the final outcome of the root canal therapy. It interferes with the proper debridement and shaping procedures as well as with irrigation of the canal portion apical to the level of obstruction. It also prevents three dimensional fluid tight sealing of the root canal system. When an attempt to bypass such a fragment becomes difficult it is advised to retrieve it by mechanical devices. Instrument removal system (IRS) is one such a device for orthograde removal of intracanal metallic obstructions. This clinical case describes the usage of IRS for retrieval of separated instrument in the posterior teeth.